2014
DOI: 10.1371/journal.pone.0104505
|View full text |Cite
|
Sign up to set email alerts
|

Snow Surface Microbiome on the High Antarctic Plateau (DOME C)

Abstract: The cryosphere is an integral part of the global climate system and one of the major habitable ecosystems of Earth's biosphere. These permanently frozen environments harbor diverse, viable and metabolically active microbial populations that represent almost all the major phylogenetic groups. In this study, we investigated the microbial diversity in the surface snow surrounding the Concordia Research Station on the High Antarctic Plateau through a polyphasic approach, including direct prokaryotic quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 58 publications
4
41
1
1
Order By: Relevance
“…The recovery of eukaryotic sequences from chloroplast sequence contamination in 16S rRNA gene analysis has been reported in a number of datasets (Michaud et al . ; Zarkasi et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery of eukaryotic sequences from chloroplast sequence contamination in 16S rRNA gene analysis has been reported in a number of datasets (Michaud et al . ; Zarkasi et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Amplicons affiliated to the chloroplast of unicellular eukaryotes were found in high abundance from seawater samples. The recovery of eukaryotic sequences from chloroplast sequence contamination in 16S rRNA gene analysis has been reported in a number of datasets (Michaud et al 2014;Zarkasi et al 2014). Haptophyceae reads are dominated by Phaeocystis globosa and account for half of the classified reads from April sea water.…”
Section: Microbial Communities In Sea Water and Fish Farm Sedimentsmentioning
confidence: 96%
“…Furthermore, the presence of microbes in remote, low-nutrient, low-water, very cold environments such as polar glacial surfaces and their snowpacks is well established [28,29]. However, the level to which microorganisms are metabolically active in the snowpack as its water content becomes scarce and temperatures drop remains contentious, as the only evidence to date remains correlative or circumstantial [19,22,30]. Research has shown that microorganisms can be incredibly persistent, even deep within high plateau polar ice, remaining culturable even after hundreds of thousands of years (see [22] references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Being in higher latitudes allows the existence of very low temperatures and high rates of solar radiation in summer. Some published reports on glacial and subglacial microbiology refer to very extreme latitudes that reach −75°S in the high Antarctic Plateau [13], −77°S in Lake Vostok [14], and −84°S in the West Antarctic ice sheet [15] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%